2018
DOI: 10.1016/j.trecan.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modifiers of the Breast Tumor Microenvironment

Abstract: Multiple nonmalignant cell types in the tumor microenvironment (TME) impact breast cancer risk, metastasis, and response to therapy, yet most heritable mechanisms that influence TME cell function and breast cancer outcomes are largely unknown. Breast cancer risk is ∼30% heritable and >170 genetic loci have been associated with breast cancer traits. However, the majority of candidate genes have poorly defined mechanistic roles in breast cancer biology. Research indicates that breast cancer risk modifiers direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 186 publications
0
35
0
Order By: Relevance
“…Kaplan-Meier analysis was performed for survival curves and the significance was determined by log-rank, during which R packages survival and survminer in R 3. 6.0 were used to analyze and sketch Kaplan-Meier curves.…”
Section: Predictive Value Of Hub Genes In Survival Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Kaplan-Meier analysis was performed for survival curves and the significance was determined by log-rank, during which R packages survival and survminer in R 3. 6.0 were used to analyze and sketch Kaplan-Meier curves.…”
Section: Predictive Value Of Hub Genes In Survival Analysismentioning
confidence: 99%
“…There are some works concerning characteristic genes that could impact tumor cellularity. Gene modifiers such as point mutations or deletions on several growth factor receptors, pattern recognition receptors, transcription factors, and apoptosis-related proteins are summarized to be associated with nonmalignant tumor microenvironment in breast cancer and affects most aspects of breast cancer biology such as tumorigenesis, progression, and metastases (6). The amount of somatic copy-number variation (SCNV) of immune genes are negatively related to immune signatures but positively related to stroma infiltration in the analysis of lung adenocarcinoma (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the tumor microenvironment, multiple juxtacrine and paracrine interactions occur between cancer and non-cancer cells impacting both BC metastasis and response to therapy [98]. The major integral components of the BC stroma are cancer-associated fibroblasts (CAFs) that drive tumor progression.…”
Section: Biogenesis and Functions Of Exosomesmentioning
confidence: 99%
“…to moderate penetrance (e.g., BRIP1, CHEK2, ATM, and PALB2, etc.) among population [317324]. These modifier alleles can be related to the malignant transformation of breast epithelial cells, where they are capable of disrupting the molecular and cellular pathways involved in regulation of many biological process [324, 325].…”
Section: Concluding Remarks the Potential Treatment Model Of Breast mentioning
confidence: 99%
“…among population [317324]. These modifier alleles can be related to the malignant transformation of breast epithelial cells, where they are capable of disrupting the molecular and cellular pathways involved in regulation of many biological process [324, 325]. The current review indicated a growing body of evidence that suggests multiple genetic modifiers of the human breast cancer, of course other modifier alleles can exist.…”
Section: Concluding Remarks the Potential Treatment Model Of Breast mentioning
confidence: 99%